BIAYA PRODUKSI KAYU LAPIS PADA BEBERAPA PERUSAHAAN DI SUMATRA SELATAN DAN KALIMANTAN SELATAN - Akub J Abdurachman; Sylviani Sylviani (Jurnal Penelitian Hasil Hutan, 1988)
A research in production cost and its distribution was conducted in several plywood manufacturers in South Sumatra and South Kalimantan. The  average, distribution and  variation  of production cost  are discussed in this report. The  results  showed  that  average cost  of  production  was  Rp  313,066  per cu.m.  with  coefficient of  variation  9% consisting of  average  fixed cost  Rp 59,135 per cu.m.  with  coefficient of  variation  19%  and  average  variable  cost Rp 253,931 per cu.m.  with  coefficient   of  variation  12%. Average profit   before  taxes  was Rp 78,827 per  cu.m.  or 26% of production cost  with  coefficient  of  variation  48%.  Due to the fact  that  the largers component   of  the cost  was used for material  expense (56%) so  it is advised  the manufacturers  should  give more care the material processing  aspect  so that  the waste  could  be reduced  as small as possible.